Large Eddy Simulations of flow around a circular cylinder close to a flat seabed. (March 2016) - Abrahamsen Prsic, Mia; Ong, Muk Chen; Pettersen, Bjørnar; Myrhaug, Dag
Abstract: Large Eddy Simulations (LES) with Smagorinsky subgrid scale model are used to study the turbulent flow and wake dynamics behind a circular cylinder close to a horizontal, plane wall at subcritical Reynolds number. The focus is on investigating the details of the flow around the cylinder placed at different distances from the wall and immersed in boundary layers of various thicknesses. The Reynolds number is Re = 13, 100. The simulations with gap to diameter ratios (G/D) of 0.2, 0.6 and 1 are carried out in order to investigate the changes of the flow field and the vortex shedding due to the presence of the plane wall. The influence of the incoming boundary layer profile is investigated through simulations with logarithmic boundary layer inlet profile of thickness 0.48D and 1.6D, and compared with a uniform inlet flow profile. 2D and 3D simulations are performed for Re ranging from 100 to 13, 100, to explore the importance of the flow three-dimensionality. The flow field in the cylinder wake, as well as the mean flow values, the spectral analysis and the pressure distribution on the cylinder surface are computed to study the flow physics due to the influences of the wall. Highlights: 3D flow around a circular cylinder in the vicinity of a plane wall at Re = 13, 100. Large Eddy Simulations with Smagorinsky subgrid scale model. Influence of the gap to diameter ratio. Influence of the boundary layer thickness. Three-dimensionality of the flow.